A study of bacterial community structure of shrimp farms along the Ratnagiri coast, Maharashtra - Bhavesh Choudhary; Anil S. Pawase; Gajanan S. Ghode; Raju M. Tibile; Varsha R. Bhatkar; Divyashree Choudhary; Utkarsh Choudhary (Heliyon)
Intensification of shrimp farming practices has increased the number and severity of disease outbreaks globally. As a result, diseases have become a significant barrier to profitable and sustainable shrimp production. Shrimp farming practices are reviving in India after its downfall in the late 90s. However, these farming practices also witness disease outbreaks due to viral and bacterial infections. Among the bacterial infections, Vibrios are the most important bacterial causative agents found in shrimp farms. They are ubiquitous and invariably seen in shrimp production conditions as opportunistic pathogens. The present study was conducted to identify the bacterial pathogens associated with the shrimp Penaeus vannamei farming systems along the Ratnagiri coast. In all, two farming units were selected: Varavade farm - a six-year-old farm, and Chinchkhari farm, a new virgin farm. The water and sediment samples were collected from January to May 2022 throughout culture period of one crop. The total plate count (TPC) of the shrimp farm water samples of the Varavade farm varied from 4.35 to 6.32 log10 CFU mL−1. In the sediments, the minimum value of TPC was 4.99 log10 CFU g−1, while the maximum value observed was 7.25 log10 CFU g−1. The Total Vibrio count (TVC) of water samples from Varavade farm varied from 4.01 to 5.63 log10 CFU mL−1. In the sediments, the minimum value of TVC was 4.64, while the maximum value observed was 6.56 log10 CFU g−1. The statistical analysis showed a significant difference in TPC and TVC (p < 0.05) among different days of culture.The TPC of the shrimp farm water samples of the Chinchkhari farm varied from 5.22 to 8.17 log10 CFU mL−1. In the sediment, the minimum value of TPC was 5.87, while the maximum value was observed at 8.45 log10 CFU g−1. The TVC of water samples from the Chinchkhari farm varied from 4.75 to 6.89 log10 CFU mL−1. In the sediment, the minimum value of TVC was 5.16, while the maximum value observed was 6.70 log10 CFU g−1. The statistical analysis showed a significant difference in TPC and TVC (p < 0.05) among different days of culture. The bacterial load was observed to increase with the progression of the culture period on both farms. The usage of probiotics, chemicals, and water exchange was observed to promote a decrease in the bacterial community.